Energy Storage and Release Through the Solar Activity Cycle 2011
DOI: 10.1007/978-1-4614-4403-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Shock Waves, EUV Waves, and Their Relation to CMEs. III. Shock-Associated CME/EUV Wave in an Event with a Two-Component EUV Transient

Abstract: On 17 January 2010, STEREO-B observed in extreme ultraviolet (EUV) and white light a large-scale dome-shaped expanding coronal transient with perfectly connected off-limb and on-disk signatures. Veronig et al. (2010, ApJL 716, 57) concluded that the dome was formed by a weak shock wave. We have revealed two EUV components, one of which corresponded to this transient. All of its properties found from EUV, white light, and a metric type II burst match expectations for a freely expanding coronal shock wave incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Note that this is consistent with the finding that metric type II bursts (which often show quasiradial propagation) tend to be faster than the laterally propagating associated waves (Warmuth, 2010;Ma et al, 2011;Grechnev et al, 2011a). The different expansion velocities could either reflect the increase of the fast-mode speed with height in the low corona (a wave or shock would speed up under these circumstances; see e.g., Grechnev et al, 2011a) or a scenario where the upper part of the disturbance is continuously driven by the erupting CME, while its flanks are freely propagation (e.g., Veronig et al, 2010).…”
Section: Lateral and Radial Kinematicssupporting
confidence: 90%
See 1 more Smart Citation
“…Note that this is consistent with the finding that metric type II bursts (which often show quasiradial propagation) tend to be faster than the laterally propagating associated waves (Warmuth, 2010;Ma et al, 2011;Grechnev et al, 2011a). The different expansion velocities could either reflect the increase of the fast-mode speed with height in the low corona (a wave or shock would speed up under these circumstances; see e.g., Grechnev et al, 2011a) or a scenario where the upper part of the disturbance is continuously driven by the erupting CME, while its flanks are freely propagation (e.g., Veronig et al, 2010).…”
Section: Lateral and Radial Kinematicssupporting
confidence: 90%
“…Analytical models based on fast-mode shocks have successfully reproduced the kinematics of coronal waves (Grechnev et al, 2008;Temmer et al, 2009;Grechnev et al, 2011b;Afanasyev and Uralov, 2011;Grechnev et al, 2011a;Temmer et al, 2013), while in the framework of numerical A more shallow signature in He i is generated in front of the main perturbation by increased irradiation, heat flux, and possibly accelerated particles from the higher parts of the inclined shock front. At the quasi-perpendicular part of the shock, a type II burst is generated.…”
Section: Small-scale Ejectamentioning
confidence: 99%
“…If the large-scale v fast distribution is strongly inhomogeneous (e.g. because of the presence of a large coronal hole), then the orientation of the axis gradually displaces toward the region of a higher v fast (Grechnev et al, 2011a(Grechnev et al, , 2013a. The shock front is "hard" like an ocean tube wave, being governed by the global wave expansion and does not depend on local inhomogeneities in the v fast distribution.…”
Section: Euv Wavementioning
confidence: 99%
“…The stronger near-surface retardation causes a tilt of the shock front sometimes observed (Hudson et al, 2003;Warmuth et al, 2004b). Local inhomogeneities in the v fast distribution over the solar surface determine the brightness of the EUV wave (Grechnev et al, 2011a), while larger inhomogeneities affect its propagation velocity and cause its reflection and refraction (e.g. Veronig et al, 2008;Gopalswamy et al, 2009;Grechnev et al, 2011b).…”
Section: Euv Wavementioning
confidence: 99%
“…The shock wave initially propagated faster at the nose than at the flanks, which corresponds to what were conceived as EIT waves. The observed kinematic behaviors have been partially reproduced in theory and models (Zhao et al, 2011;Grechnev et al, 2011;Temmer, Vrsnak, and Veronig, 2013) of the 17 January 2010 event reported by Veronig et al (2010). For the 13 June 2010 event, Kouloumvakos et al (2014) concluded that both the nose and flank of the CME drove the shock.…”
Section: Discussionmentioning
confidence: 60%